Food Habits and Niche Breadth of Three Species of Fish Catchs in Aneuk Laot Lake, Sabang Aceh - Nurfadillah Nurfadillah; Irma Dewiyanti; Muhammad Akbar Maulana; Siswani Sari; Hasfiandi Hasfiandi (Elkawnie: Journal of Islamic Science and Technology, 2022)
Abstract: Aneuk Laot Lake becomes a source of livelihood for people who work as fishermen around the lake. This research was conducted in June 2020. The study aims to analyze the food habits, niche breadth, and niche overlap of tilapia (Oreochromis niloticus), mujair (Oreochromis mossambicus), and louhan (Cichlasoma trimaculatum) in Aneuk Laot Lake. The method used in this study is the survey method. Fishing is done with the use of ring trawls of 2 and 3 inches. Tilapia, Mujair, and Louhan fish that have been caught were dissected and their digestive organs were preserved using 10% NBF. The results showed that Tilapia (O. niloticus) are omnivorous with phytoplankton as their main food and an index of preponderance value of 54.72%, Mujair (O. mossambicus) are omnivorous with the main food in the form of phytoplankton and the index of preponderance value is 50.15%, and louhan (C. trimaculatum) is carnivorous with the main food in the form of small fish and the index of preponderance value is 99.35%. The value of the niche breadth of Tilapia is 2.89, Mujair is 2.66, and Louhan is 1.07. The niche overlap value of food between Tilapia and Mujair is 0.96, meaning that it has great potential to utilize the same type of food, whereas Louhan's niche overlap index with Nila and Mujair is 0.01, indicating that it has very little competition in using the same food.Abstrak: Danau Aneuk Laot menjadi sumber mata pencaharian bagi masyarakat yang berprofesi sebagai nelayan di sekitar danau. Penelitian ini dilaksanakan pada bulan Juni 2020 di Danau Aneuk Laot, Sabang. Penelitian ini bertujuan untuk menganalisis kebiasaan makan, luas relung, dan tumpang tindih makanan ikan nila (Oreochromis niloticus), mujair (Oreochromis mossambicus), dan louhan (Cichlasoma trimaculatum) di Danau Aneuk Laot. Metode yang digunakan dalam penelitian ini adalah metode survei. Penangkapan ikan dilakukan dengan menggunakan pukat cincin ukuran 2 dan 3 inchi. Ikan Nila, Mujair, dan Louhan yang telah ditangkap dibedah dan organ pencernaannya diawetkan menggunakan NBF 10%. Hasil penelitian menunjukkan bahwa ikan Nila (O. niloticus) adalah omnivora dengan makanan utama fitoplankton dan nilai indeks preponderance sebesar 54,72%, Mujair (O. mossambicus) adalah omnivora dengan makanan utama berupa fitoplankton dan indeks nilai preponderance adalah 50,15%, dan Louhan (C. trimaculatum) merupakan karnivora dengan makanan utama berupa ikan-ikan kecil dan indeks nilai preponderance sebesar 99,35%. Nilai luas relung Nila sebesar 2,89, Mujair sebesar 2,66, dan Louhan sebesar 1,07. Nilai tumpang tindih makanan antara Nila dan Mujair sebesar 0,96 artinya memiliki  potensi yang besar dalam memanfaatkan jenis makanan yang sama sedangkan indeks tumpang tindih Louhan dengan Nila dan Mujair sebesar 0,01 yang berarti memiliki kompetisi yang sangat kecil dalam memanfaatkan makanan yang sama.